Analysis of the long-term effects of solar radiation on the indoor thermal comfort in office buildings. (15th May 2022) - Song, Bing; Bai, Lujian; Yang, Liu
Abstract: Windows play a critical role in building energy consumption and thermal comfort. Although many different models have been adopted for developing standards for indoor thermal comfort evaluation, the impact of solar radiation on occupant thermal sensation is still overlooked. In this study, the SMRT-Air temperature deviation method, in which the impact of solar radiation can be assessed based on the deviation of the solar-adjusted mean radiant temperature from air temperature, was developed to help the designer conveniently evaluate the impact of solar radiation on indoor thermal comfort in initial design stage. This method was applied to evaluate the effect of solar radiation on occupants in office buildings under different orientation and climate zones in China. The results show that the effect of solar radiation on thermal comfort is more severe in cold climate zones. Controlling the amount of solar radiation transmitted by windows facing east and west is more critical than for windows oriented in other directions. An appropriate decrease SHGC of windows from the current standard requirements can reduce over 86% discomfort times when SHGC decrease to 0.3 in all climate zones. The outcomes of this study can help designers implement appropriate measures for improving indoor thermal comfort. Highlights: A new method was developed to quickly evaluate the impact of solar radiation on thermal comfort indoors. The long-term effect of solar radiation on indoor thermal comfort was quantitatively accessed. Different thermal discomfort degrees distributed spatial indoor were observed.